Molecular Characterization and Comparative Genomic Analysis of vB_PaeP_YA3, a Novel Temperate Bacteriophage of Pseudomonas aeruginosa - Yu, Xinyan; Xu, Jing; Gu, Yu; Zhang, Ruiyang; Zhu, Yefei; Liu, Xiaoqiu (Frontiers in Microbiology, 2020)
It is well-known that bacteriophages play crucial roles in many aspects, such as controlling the number and diversity of bacteria, and participating in horizontal gene transfer which is a key process in the evolution of bacteria. But so far, the number of temperate bacteriophages was still limited, and their life processes were severely unknown except members of the lambdoid family of coliphages. In this study, a novel temperate phage of Pseudomonas aeruginosa, YA3 (vB_PaeP_YA3), was isolated from waste water. The morphology of YA3 suggested that it is a Podoviridae. The YA3 genome is a circular double-stranded DNA of 45,253 bp with an average G+C content of 57.2%. Total 65 open reading frames (ORFs) were predicted according to the sequence of YA3’s genome, of which only 32 (49.2%) ORFs were assigned with putative functions and 13 ORFs were confirmed by the structural proteome. Genome and proteome analyses confirmed the lysogenic nature of this phage, which encodes typical lysogen related proteins integrase, CI, Cro and Q protein. The genome of YA3 is most closely related with that of temperate phage vB_PaeP_Tr60_Ab31, whereas the homology coverage is just 48%. There are many critical differences between their genomes, involving promoters, lysis pathways and regulation patterns. YA3 is capable of stably lysogenizing its host Pseudomonas aeruginosa PA14, targeting the integration site within the serine tRNA gene (PA14_RS20820), which is similar with phage vB_PaeP_Tr60_Ab31. The phylogenetic analysis is more complicated than we thought. Based on phage terminase large subunit (TerL) and CI proteins, phage YA3 is related with phage lambda, while their genome coverage is extremely low (<1%). Therefore, phage YA3 is a considerably novel lambda-like temperate phage, and further study of its genome may deepen our understanding of interaction between lysogenic phages and their bacterial hosts.